2019
DOI: 10.1016/j.cortex.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the language control network in bilingual visual word recognition

Abstract: Research into bilingual language production has identified a language control network that subserves control operations when bilinguals produce speech. Here we explore which brain areas are recruited for control purposes in bilingual language comprehension. In two experimental fMRI sessions, Dutch-English unbalanced bilinguals read words that differed in cross-linguistic form and meaning overlap across their two languages. The need for control operations was further manipulated by varying stimulus list composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…The facilitation effects for identical cognates observed in the pure list and the inhibition effects in the mixed list support this interpretation. This pattern of results for identical cognates further mirrors the findings of a recent fMRI study with the same set of cognates and interlingual homographs that was conducted in parallel with the present study (Peeters et al, 2019). In that study, identical cognates reliably activated the language control network (Abutalebi & Green, 2016) in a mixed list context, but not in a pure task situation.…”
Section: English Lexical Decision Without and With Pure Dutch Wordssupporting
confidence: 91%
See 2 more Smart Citations
“…The facilitation effects for identical cognates observed in the pure list and the inhibition effects in the mixed list support this interpretation. This pattern of results for identical cognates further mirrors the findings of a recent fMRI study with the same set of cognates and interlingual homographs that was conducted in parallel with the present study (Peeters et al, 2019). In that study, identical cognates reliably activated the language control network (Abutalebi & Green, 2016) in a mixed list context, but not in a pure task situation.…”
Section: English Lexical Decision Without and With Pure Dutch Wordssupporting
confidence: 91%
“…This was exactly what was observed in the present study. As reported above, recent neuroimaging findings (Peeters et al, 2019) indeed reveal that non-identical cognates do not reliably activate the language control network in a mixed list context, whereas identical cognates do.…”
Section: English Lexical Decision Without and With Pure Dutch Wordsmentioning
confidence: 57%
See 1 more Smart Citation
“…Following brain damage, the competitive process (possibly of inhibitory nature) for lexical selection in the non-dominant language could be affected and this would explain why patients are more impaired in that language. Previous neuroimaging studies in bilinguals found mixed results: some that the control network described for language production (Abutalebi and Green, 2007, 2016; Calabria et al, 2018) is also active during word comprehension and recognition tasks (Peeters et al, 2019), but some other studies suggest that the overlap between the two system is only partial (Abutalebi et al, 2007; Blanco-Elorrieta and Pylkkänen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This issue is relevant in the broader context of the widely debated extent of overlap between brain networks and neurocognitive mechanisms functionally involved in executive control and language control. Neuroimaging work indicates that the language control network, which subserves control operations when bilinguals produce (Abutalebi & Green, 2008Luk, Green, Abutalebi, & Grady, 2012) and comprehend language (Peeters, Vanlangendonck, Rueschemeyer, & Dijkstra, 2019), overlaps with the network implicated in executive control more generally (e.g., Abutalebi et al, 2011;Blanco-Elorrieta & Pylkkänen, 2016, 2017Branzi, Della Rosa, Canini, Costa, & Abutalebi, 2016;De Baene, Duyck, Brass, & Carreiras, 2015;De Bruin et al, 2014;Coderre, Smith, Van Heuven, & Horwitz, 2016;Garbin et al, 2010;Grant, Fang, & Li, 2015;Green & Abutalebi, 2013). The exact degree of overlap, however, is under debate and views differ in whether they posit only partial overlap (e.g., Calabria, Baus, & Costa, 2019;Magezi, Khateb, Mouthon, Spierer, & Annoni, 2012;Timmer, Calabria, Branzi, Baus, & Costa, 2018;Weissberger, Wierenga, Bondi, & Gollan, 2012) or significant overlap between highly similar brain circuits (e.g., Abutalebi & Green, 2016;De Baene et al, 2015;Pliatsikas & Luk, 2016).…”
Section: Switching Languages Versus Switching Listenersmentioning
confidence: 99%